Public tendering practices, issues and directions - a case of Pakistan construction sector - Khoso, Ali Raza; Yusof, Md Aminah; Leghari, Muhammad Aslam; Siddiqui, Fida; Sohu, Samiullah (Universiti Putra Malaysia Press, 2021)
Outdated tendering system is a significant obstacle in the momentum of public sector development in Pakistan. This study aims to examine various undiscovered part of public tendering through a detailed survey from key professionals, experts, and decision-makers of public projects. Furthermore, research covers the present status of public tendering in Pakistan and provides recommendations as per experts’ opinion. This paper exhaustively highlights how the classical customs of the public tendering in Pakistan could track the old-fashioned sector to an upright path. Intensive interviews and questionnaire surveys were carried out throughout the country for data compilation. The one-way ANOVA test was performed to verify the perception of various participants and to reject the null hypothesis. The study revealed various interesting facts of present-day situations of public tendering. Various pitfalls in public tendering were underlined in the speculation of experts. The study concluded that public tendering in Pakistan is crowded with severe threats that may be alarming for the future of the industry. Un-discovering of alarming facts about public tendering in Pakistan opens the directions for several researchers in terms of exploring project case studies further. The research is an eye-opener for policymakers, experts, decision-makers and governmental bodies to regulate the public tendering system accordingly.